Compassionate extubation for a peaceful death in the setting of a community hospital: a case-series study - Kok VC (Clinical Interventions in Aging, 2015)
Victor C Kok1,2 1Division of Palliative Medicine and Hospice Palliative Care Team, Kuang Tien General Hospital, 2Department of Biomedical Informatics, Asia University Taiwan, Taichung, Taiwan Background: The use of compassionate extubation (CE) to alleviate suffering by terminating mechanical ventilation and withdrawing the endotracheal tube requires professional adherence and efficiency. The Hospice Palliative Care Act, amended on January 9, 2013, legalizes the CE procedure in Taiwan. Methods: From September 20, 2013 to September 2, 2014, the hospice palliative care team at a community hospital received 20 consultations for CE. Eight cases were excluded because of non-qualification. Following approval from the Ethics Committee, the medical records of the remaining 12 patients were reviewed and grouped by the underlying disease: A, “terminal-stage cancer”; B, “non-cancer out-of-hospital cardiac arrest”; and C, “non-cancer organ failure”. Time to extubation using a cut-off at 48 hours was assessed. Results: The mean ages of patients (standard deviation) in groups A, B, and C were 66.3 (14.9) years, 72 (19.1) years, and 80.3 (4.0) years, respectively. The mean number of days of intubation at consultation were 6.8 (4.9), 7.3 (4.9), and 179.3 (271.6), respectively. The mean total doses of opioids (as morphine-equivalent dose) in the 24 hours preceding CE were 76 (87.5) mg, 3.3 (5.8) mg, and 43.3 (15.3) mg. The median times from extubation (range) to death were 97 (0.2–245) hours, 0.3 (0.2–0.4) hours, and 6.1 (3.6–71.8) hours. Compared to those requiring <48-hour preparatory time, patients requiring >48 hours to the moment of CE were younger (62.8 years vs 75.5 years), required a mean time of 122 hours (vs 30 hours) to CE (P=0.004), had shorter length of stay (33.3 days vs 77.8 days), required specialist social worker intervention in 75% of cases (vs 37.5%), and had a median duration of intubation of 11.5 days (vs 5.5 days). Conclusion: CE was carried out according to protocol, and the median time from extubation to death varies determined by the underlying disease which was 0.3 hour in patients admitted after out-of-hospital cardiac arrest and 97 hours in patients with advanced cancer. Keywords: compassionate extubation, palliative extubation, good death, hospice care, quality of death